The Neuroprotective Effects of Thymoquinone: A Review - Tahereh Farkhondeh; Saeed Samarghandian; Ali Mohammad Pourbagher Shahri; Fariborz Samini (SAGE Publishing, 2018)
Thymoquinone (TQ), one of the main components active of Nigella sativa , exhibited very useful biomedical effects such as anti-inflammatory, antioxidant, antimicrobial, antiparasitic, anticancer, hypoglycemic, antihypertensive, and antiasthmatic effects. There are several studies about pharmacological activities of TQ but its neuroprotection effects are not fully described. The literature search has indicated many studies pertaining to the effects of TQ in neurological problems such as epilepsy, parkinsonism, anxiety, and improvement of learning and memory, and so on. In addition, TQ protected brain cells from various injuries due to its antioxidant, anti-inflammatory, and apoptotic effects in cell line and experimental animal models. The present study has been designed to review the scientific literature about the pharmacological activities of TQ to the neurological diseases. This study purposed that although experimental studies indicated the beneficial effects of TQ against nervous system problems, better designed clinical trials in humans are needed to confirm these effects.